2019
DOI: 10.33795/j-adbis.v12i2.49
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Orientasi Belanja Dan Perbedaan Gender Terhadap Pencarian Informasi Online Dan Belanja Online Pada Mahasiswa Jurusan Administrasi Niaga Politeknik Negeri Malang

Abstract: This study aims to determine the effect of shopping orientation on online information search and online shopping, as well as differences in men and women in shopping orientation. The type of research used in this study is quantitative research with descriptive causal types. The study population was students of the 2017/2018 Academic Year of Malang State Polytechnic who had made an online purchase. Data collection uses a questionnaire to 94 respondents using purposive random sampling technique. Data analysis us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Consumer can search and compare products or services that match the wishes and abilities of these consumers. They also use internet facilities to search for information about the products they want (Sudjanarti et al, 2018). Previous research on consumers' shopping orientations in the context of Internet shopping indicated that consumers who had distinct shopping orientations had different shopping behaviours while shopping online (Seock & Bailey, 2008).…”
Section: Online Shoppingmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer can search and compare products or services that match the wishes and abilities of these consumers. They also use internet facilities to search for information about the products they want (Sudjanarti et al, 2018). Previous research on consumers' shopping orientations in the context of Internet shopping indicated that consumers who had distinct shopping orientations had different shopping behaviours while shopping online (Seock & Bailey, 2008).…”
Section: Online Shoppingmentioning
confidence: 99%
“…While, studies of online shopping attitude are widespread in the literature, studies of gender differences in online shopping attitude are scarce and reported findings are inconsistent (Dittmar et al, 2004;Hasan, 2010). Gender is the factor that distinguishes the frequency of online purchases (Sudjanarti et al, 2018). This is supported by Rodgers & Harris, (2003) that the number of Internet users is equally divided among the genders, more men than women engage in online shopping and make online purchases.…”
Section: Introductionmentioning
confidence: 99%
“…Hal tersebut dapat dipahami karena laki-laki lebih sering menggunakan media sosial, dimana online shopping membuat konsumen semakin mudah untuk berbelanja tanpa harus menghabiskan waktu serta tenaga (Selwendri & Siregar, 2018). Sedangkan, menurut kodratnya, perempuan adalah sosok yang senang berbelanja dibandingkan membuka usaha untuk berbisnis (Sudjanarti, Khabibah, & Wardani, 2019). Sehingga, berdasarkan hal tersebut dapat disimpulkan bahwa jelas laki-laki lebih sering menggunakan media sosial untuk keperluan belanja atau berbisnis.…”
Section: Hasil Dan Pembahasanunclassified
“…Uji Independent Sample T-Test menurut (Santoso, 2014) merupakan uji yang menggunakan metode perbandingan antara dua kelompok mean dari dua sampel yang berbeda (independent). Pada prinsipnya uji Independent Sample T-Test berfungsi untuk mengetahui apakah ada perbedaan mean antara dua populasi dengan membandingkan dua mean sampelnya.…”
Section: Uji Independent Simple T Testunclassified